A Priori Knowledge Based GMTI Algorithm For Traffic Monitoring Applications - Baumgartner, Stefan; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
In the paper a ground moving target indication and parameter estimation algorithm applicable on single-as well as on multi-channel airborne synthetic aperture radar data is presented. The algorithm is based on a priori knowledge and operates directly on range-compressed data. Only the intersection points of the moving vehicle signals with the a priori known road axes, which are mapped into the range-compressed data domain, are evaluated. The algorithm needs low computational power and, hence, it is suitable for real-time traffic monitoring applications. The absolute velocities, the headings and the geocoded positions of the detected moving vehicles can be estimated. A verification of the algorithm is done using real dual-channel data acquired with DLR's new airborne system F-SAR.
DLR Import::2019-04-03